the Physical Condition Study of Football Players at SMP Negeri 20 Kerinci: Physical Condition Study of Football Players at SMP Negeri 20 Kerinci - Doki Harpinus; Acep Rohmat Nurhidayat; Aidil Putra; Rahmat Gunawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the physical condition of football players at SMP Negeri 20 Kerinci. The research method used in this study uses a quantitative method with a descriptive research type. This descriptive study analyzes and describes the physical condition of football players at SMP Negeri 20 Kerinci. Participants in this study were 35 players who represented the population. The results of the study found that out of 35 football players at SMP Negeri 20 Kerinci who had physical conditions, only 2 people (5.71%) were in the very good category and 10 people (28.57%) were in the good category. 9 people (25.71%) were in the moderate category, 13 people (37.14%) were in the poor category, 1 person (2.86%) was in the very poor category. This means that most players do not have good physical conditions. As a player or athlete, it is important to have good physical conditions so that performance during the match is optimal.